Pengaruh E-Service Quality dan Customer Satisfaction Terhadap Customer Loyality pada Tiktok Shop : Studi Kasus Mahasiswa Fakultas Ekonomi UNUSIDA - Zainiyah, Alfidhotul; Irsyadia, Latifah; Kiromi, Mukhammad Nuzulul; Kamila, Edita Rachma (Universitas Multi Data Palembang, 2025)
This study aims to analyze the effect of E-Service Quality and Customer Satisfaction on Customer Loyalty on the TikTok Shop platform. With a quantitative approach, data was collected through a survey of 100 respondents who were students of the Faculty of Economics, Nahdlatul Ulama University, Sidoarjo. The analysis was carried out using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method. The results showed that E-Service Quality and Customer Satisfaction have a positive and significant influence on Customer Loyalty. Partially, Customer Satisfaction has a greater influence than E-Service Quality. Simultaneously, both variables contribute significantly to increasing customer loyalty, with the dominant role of Customer Satisfaction. This research underscores the importance of TikTok Shop to improve efficient and secure e-service quality, and focus on customer satisfaction through an optimal shopping experience. The findings provide strategic insights for e-commerce businesses in increasing customer loyalty.